Acceptance Towards COVID-19 Vaccination in Breast Cancer Patients: An Analytical Cross-Sectional Study in A Tertiary Care Hospital of Rawalpindi, Pakistan - Malik, Asmara Ahmed; Zubaida Rashid; Syeda Rifaat Qamar Naqvi; Mommana Ali Rathore; Nadia Ramzan (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the level of COVID-19 vaccine acceptance among patients diagnosed with breast cancer.Study Design: Analytical cross-sectional.Place and Duration of Study: The study was conducted in Breast Cancer Outpatient Department located in a tertiary care hospital in Rawalpindi, Pakistan from Nov 2021 to Jul 2022.Methodology: Validated questionnaire was used to collect data from patients diagnosed with breast cancer. Sample size of n=134 was attained using non-probability consecutive sampling. Data was analyzed using SPSS version 22. A p-value of